Association between serum uric acid and nonalcoholic fatty liver disease in the US population - Shih, Ming-Hsiung (J Formos Med Assoc, 2013)
BACKGROUND/PURPOSE: Studies conducted in Eastern Asia suggest that serum uric acid (SUA) level is highly related to nonalcoholic fatty liver disease (NAFLD). However, limited information is available in the USA. Our objective was to determine the association between NAFLD and SUA levels in the USA and to determine if this is independent of age, sex, and components of metabolic syndrome (MetS). METHODS: We analyzed 5370 men and women aged 20–74 years from the Third National Health and Nutrition Examination Survey (NHANES III) (1988–1994) in the USA. We calculated the prevalence and odds ratio (OR) of NAFLD and elevated liver enzymes by SUA and sex-specific quin-tiles of SUA, adjusting for multiple factors. RESULTS: The prevalence of NAFLD was higher in participants with higher SUA levels (10.9%,9.6%, 15.9%, 21.8% and 33.1%, respectively, from the second to the fifth sex-specific quintile of uric acid). After adjustment, individuals with hyperuricemia were more likely to have NAFLD (OR: 1.4, 95% CI: 1.1–1.9). Similarly, the adjusted odds of NAFLD were increasingly higher from the second to the fifth quintile of SUA (ORs: 0.8, 1.2, 1.5 and 1.7, respectively; p < 0.01) as compared to the lowest quintile. Finally, individuals with hyperuricemia were more likely to have elevated liver enzymes (aspartate aminotransferase or alanine aminotransferase) (adjusted OR: 1.8, 95% CI: 1.1–2.7). CONCLUSION: NAFLD and SUA levels were strongly and independently associated in this nationally representative sample of men and women after adjustment for multiple factors.